2022
DOI: 10.3390/vaccines10060872
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Pertussis in Adults at Childbearing Age Pre- and Post- COVID-19 in Beijing, China

Abstract: The number of reported pertussis cases has significantly decreased during the coronavirus disease 2019 (COVID-19) pandemic under the influence of strict public health measures in many countries including China. This study evaluated the prevalence of serum anti-pertussis toxin (anti-PT) IgG antibodies in adults at childbearing age pre- and post- COVID-19 in Beijing, China. Altogether, 2021 serum samples collected from individuals aged 20 to 39 years who attended an annual health examination at the Sixth Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Similar situations were observed in other regions, with estimated pertussis infection rates as follows: 7290/100,000 in Chongqing [ 19 ], 4573/100,000 in Ningbo [ 7 ], 9395/100,000 in Guangdong [ 25 ], 18080/100,000 in Jiangsu [ 17 ], and 6600/100,000 in the Netherlands [ 4 ]. Meanwhile, this study revealed a high susceptibility rate of 40.49% for individuals with Anti-PT-lgG <5 IU/mL, consistent with findings from multiple studies [ 17 , 18 , 28 ]. This indicates a coexistence of high infection rates and susceptibility in the population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar situations were observed in other regions, with estimated pertussis infection rates as follows: 7290/100,000 in Chongqing [ 19 ], 4573/100,000 in Ningbo [ 7 ], 9395/100,000 in Guangdong [ 25 ], 18080/100,000 in Jiangsu [ 17 ], and 6600/100,000 in the Netherlands [ 4 ]. Meanwhile, this study revealed a high susceptibility rate of 40.49% for individuals with Anti-PT-lgG <5 IU/mL, consistent with findings from multiple studies [ 17 , 18 , 28 ]. This indicates a coexistence of high infection rates and susceptibility in the population.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the susceptibility rate of women of childbearing age (15–49 years old) is as high as 54.88%, with a GMC of only 7.71 IU/mL, indicating a low level of Anti-PT-lgG in maternal antibodies. Chen et al’s study [ 28 ] found that the proportion of women of childbearing age with Anti-PT-lgG <5 IU/mL was 66.66%, 65.99%, and 70.24% in the years 2018–2020, showing an increasing trend in susceptibility. The median Anti-PT-lgG in 2020 was significantly lower than the pre-pandemic levels in 2018 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with anti-PT IgG antibodies higher than 40 IU/mL were 7.70% from the total sample (90/1169). A recent study that was conducted in China recorded positive pertussis antibodies in 1.79% in 2018, 2.04% in 2019, and finally 1.66% in 2020, respectively [27]. A cross-sectional retrospective seroprevalence study among middle-aged adults in 18 EU/EEA countries, including Greece, showed that there is circulation of B. pertussis, despite highly implemented childhood vaccination programs [28].…”
Section: Discussionmentioning
confidence: 99%
“…We used the cut-offs ≥62.5 IU/mL and ≥125 IU/mL as a pertussis infection within 12 months and 6 months, respectively, following previous studies [ 16 , 18 , 19 , 20 , 21 ] so that we can compare our results with those studies. We noted that some studies have used different cut-off values [ 23 , 40 ]; therefore, the prevalence of recent infections would differ by using different cut-off values. However, we believe that our finding of substantial circulation of B. pertussis in the community and its risk factors would not change.…”
Section: Discussionmentioning
confidence: 99%